Cannabidiol combined with GABAergic drugs but not with sodium channel blockers prevents the development of drug-resistance seizures in a preclinical model - Fuentes-Mejia, Monserrat; Fallico, Maximiliano J.; Talevi, Alan; Gavernet, Luciana; Orozco-Suárez, Sandra A.; Rocha, Luisa (Frontiers in Pharmacology, 2025)
Drug resistance affects 30% of patients with epilepsy. Cannabidiol (CBD) decreases the expression of drug-resistant seizures in specific syndromes. However, it is unknown if CBD prevents the development of drug-resistant condition in epilepsy. This research was conducted to investigate if subchronic administration of CBD with sodium channel blockers modifies the mortality associated with clonic-tonic seizures and the development of the drug-resistant phenotype induced by subchronic administration of 3-mercaptopropionic acid (3-MP) in rats. These effects were compared with those elicited by antiseizure medications acting on the GABAA receptors. Male Wistar rats were used to evaluate CBD combined with different antiseizure medications (phenobarbital, diazepam, valproic acid, lamotrigine and oxcarbazepine) during the repetitive administration of 3-MP. The mortality rate and development of drug-resistant seizures were estimated. Computational experiments explored interactions between CBD and sodium channel blockers in the NaV1.7 receptor. Subchronic administration of CBD alone did not modify neither the mortality rate nor the development of drug-resistant seizures. CBD combined with phenobarbital or diazepam reduced the mortality rate and prevalence of drug-resistant seizures. In contrast, coadministration of CBD with valproic acid or lamotrigine did not modify neither the mortality rate nor the expression of drug-resistant seizures. Contrariwise, combining CBD with oxcarbazepine at ED50 increases the incidence of drug-resistant seizures. Computational experiments suggested that CBD acting on NaV1.7 interferes with the action of sodium channel blockers and precludes their inhibitory effects. Our results indicate that repeated administration of CBD with GABAergic antiseizure medications, but not sodium channel blockers, decreases the mortality and prevents the development of the drug-resistant phenotype induced by repeatedly provoked severe seizures.